Studi Dinamika Kelompok Nelayan dan Kelompok Pembudidaya di Desa Muara Badak Ilir Kecamatan Muara Badak Kabupaten Kutai Kartanegara - Syamsuri; Erwiantono; Wahyu Fahrizal (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
The purpose of this study was to determine the profile of fisherman and cultivator groups and the level of dynamics of fisherman and cultivator groups in Muara Badak Ilir Village, Muara Badak District, Kutai Kartanegara Regency. The sample method used is purposive sampling method and the data analysis used is descriptive qualitative analysis and Likert scale. The results of the analysis show the characteristics of the management and members of the fishermen and cultivator groups, including the age group of 41 – 56 years, the majority of which are elementary school education, non-formal education 1 – 2 meetings, income is around 2,100,000 – 3,000,000, the majority have joined 9 – 11 years and married. The level of dynamics of the fishermen group is entering the class is quite dynamic, while for the cultivator group entering the class is quite dynamic and dynamic.